Предмет: Алгебра,
автор: bitch4
x(x+2)-3x-6=0 как решить
Ответы
Автор ответа:
0
x(x+2)-3x-6=0
x²+2x-3x-6=0 раскрываем скобки
x²-x-6=0 приводим подобные
D=b²-4ac=1-4*(-6)=25 находим дискриминант
x¹'²=(-b±√D)/2a
x¹'²=(1±5)/2
x¹=3
x²=-2
x²+2x-3x-6=0 раскрываем скобки
x²-x-6=0 приводим подобные
D=b²-4ac=1-4*(-6)=25 находим дискриминант
x¹'²=(-b±√D)/2a
x¹'²=(1±5)/2
x¹=3
x²=-2
Похожие вопросы
Предмет: География,
автор: kenjebaevaasem08
Предмет: Математика,
автор: saselandrej89
Предмет: Математика,
автор: viktoriasepetkova899
Предмет: Математика,
автор: flux2014
Предмет: Обществознание,
автор: alenchy